Lactoferrin in the Prevention of Recurrent Respiratory Infections in Preschool Children: A Prospective Randomized Study - Angela Pasinato; Mario Fama; Giovanni Tripepi; Colin Gerard Egan; Eugenio Baraldi (MDPI AG, 2024)
Few studies have evaluated the effect of bovine lactoferrin (bLf) on reducing respiratory infections in preschool children. This randomized controlled trial evaluated the effect of bLf in preschool children with recurrent respiratory infections. Participants were randomly assigned bLf (n = 25) or control (n = 25). Outcomes included respiratory infection episodes (RIEs), symptom duration, school absence and medication. Fifty children aged 4.2 ± 0.1 years were included. During the active 4-month phase, median number of RIEs was reduced by 50% in the bLf group [1-episode, interquartile range (IQR): 0-2] vs. control (2, IQR: 1-3; p = 0.02). The proportion of participants with >3 RIEs was significantly lower in bLf (n = 1, 4%) vs. control (n = 7, 28%) with 80% lower odds of upper RIEs in the bLf arm (odds ratio: 0.20, 95% CI:0.06-0.74, p = 0.015). The duration of symptoms (3 vs. 6, p = 0.009) and days absent from school (3 vs. 6, p = 0.15) were lower in the active arm. Over the 2-month follow-up, no significant differences were observed between groups for infection episodes, symptom duration or school absence. However, bLf-treated children received significantly less corticosteroids over the entire 6-month study period (32% vs. 60%; p = 0.047). bLf supplementation significantly reduced the frequency and duration of RIEs in children with decreased corticosteroid use.